DINAMIKA PENETAPAN GELAR ADAT OLEH LEMBAGA ADAT MELAYU (LAM) RIAU TAHUN 2018 - Fitri, Rizka; Asrida, Wan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Based on the Regional Regulation of Riau Province Number 1 of 2012 about the Malay Custom Institution of Riau in Chapter 17 Verse 3 statesthat the institution may give customary degree to the decent figures according to their services to the community and Riau region. Moreover, Chapter 29 Verse 1 of the institution Bylaws states that the institution may give the degree to the figures based on their plot, decent, and properness. The degree is divided into two: the Customary Degree and the Honor Customary Degree. Afterwards, the determination process of the customary degree by the institution is carried out through four main steps: pre-degree awarding, selection, endorsement and confirmation. The study aims to (1) to describe the dynamic of customary degree determination by the Malay Custom Institution of Riau in 2018: Ustadz H. Abdul Somad, Lc., M.A; H. Sutardji Calzoum Bachri; Ir. H. Joko Widodo. (2) to describe some factors which affect the degree determination by the Malay Custom Institution of Riau in 2018:Ustadz H. Abdul Somad, Lc., M.A;H. Sutardji Calzoum Bachri;Ir. H. Joko Widodo. Furthermore, the study employed a qualitative research method. The data were collected from the research informant, documents, and printed media. The data were collected through interview and documentation. While the data were analyzed by using qualitative data analysis technique. The findings of the study show that the dynamic of customary degree determination which was carried out by the Malay Custom Institution of Riau to Ustadz H. Abdul Somad, Lc., M.A dan H. Sutardji Calzoum Bachriwas procedurally correct, while the degree to Ir. H. Joko Widodo was not. The involvement of the institution in politics has led to various counter responses from the members of the institution, Riau Community Organizations, Riau non-governmental organizations, and Riau activists. Some factors which affected the determination were because of the services from each of those figures and the political interest from one of them. Keywords: Formulation, Dynamic, Custom Institution